Improvement of microstructure of bovine hydroxyapatite (BHA) with machineable fluorapatite glass (MFG) - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2008)
Composites of calcinated bovine bone derived hydroxyapatite (BHA) doped with 5 wt% and 10 wt% rnachineable fluorapatite glass (MFG) were prepared by sintering. Microstructure observations and measurements of density, compression strength and microhardness indicated a positive effect of MFG-doping to BHA. The highest compression strength (59.7 MPa) was achieved after sintering at 1300 degrees C for 5% MFG. In the light of results of earlier similar studies, the paper discusses the features of the potential of BHA-MFG composites in biomedical practice.
Keywords: hydroxyapatite; machineable fluorapatite glass; sintering; microstructure; mechanical properties; MECHANICAL-PROPERTIES; COMPOSITES